PENGARUH SELF-EFFICACY TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP NEGERI 2 PADANGSIDIMPUAN - Rahmatika Elindra; Eva Yanti Siregar; Maya sahrona (JURNAL MathEdu (Mathematic Education Journal), 2023)
This study aims to determine whether there is a significant influence between self-efficacy on the mathematical communication abilities of students of SMP Negeri 2 Padangsidimpuan. This type of research used quantitative by applying descriptive method. The population in this study were all students of class VII SMP Negeri 2 Padangsidimpuan which consisted of 11 classes totaling 352 students. The sample of this research was 32 students in class VII-8 who were taken using random sampling technique. Questionnaires and tests were used in data collection. Descriptive analysis by using SPSS 22 software shows the average of student self-efficacy was 74.31 (medium category). The average of students' mathematical communication skills is 66.569 (enough category). Furthermore, by using t-test (SPSS 22) shows significance is less than 0.05 (0.000 <0.05) or t-calculated is greater than t-table (9.739 ˃ 2.042). Means that the alternative hypothesis is accepted. The other words there is a significant influence between Self-Efficacy on the mathematical communication skills of SMP Negeri 2 Padangsidimpuan students